Hegels Begriff der Gewohnheit: zwischen Philosophie des Geistes und Ästhetik - Peters, Julia (Deutsche Zeitschrift für Philosophie, 2018)
In his Encyclopedia of Philosophical Sciences , Hegel states that the essential characteristic of spirit is to exhibit the structure of manifestation. This paper argues that for Hegel the structure of manifestation is actualized in habituated bodily actions, which sheds light on Hegel’s understanding of the relation between body and soul. Furthermore, the paper shows that there is an intrinsic relation between Hegel’s theory of habit and his aesthetics. Insofar as it exemplifies the structure of manifestation, habit has an expressive dimension for Hegel, and is therefore essentially complemented by its portrayal in classical works of art by virtue of the specific relation between form and content that such works exhibit. According to the interpretation presented here, Hegel’s philosophy of mind and his philosophy of aesthetics mutually complement and illuminate each other.
Gesehen am 30.11.2022
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831